Front Cover: PPICurator: A Tool for Extracting Comprehensive Protein–Protein Interaction Information. Issue 4 (15th February 2019) - Li, Mansheng; He, Qiang; Ma, Jie; He, Fuchu; Zhu, Yunping; Chang, Cheng; Chen, Tao
Abstract : DOI:10.1002/pmic.201800291 The PPICurator is a tool that automates the extraction of comprehensive PPI information through literature, including PPI relations, as well as their confidential scores, interaction directions, effects and functional annotations. The PPICurator will provide significant support for researchers and practitioners in the field of PPI. More details can be found in the article number1800291 by Li et al. The cover design shows the architecture of the PPICurator, which is composed of four functional modules, the Abstract Localization & Update module, the Retrieval & Filter module, the PPI Information Extraction & Enrichment module and the Output & Visualization module.